Sowing Seeds in the City 2016
DOI: 10.1007/978-94-017-7456-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Health in the Garden

Abstract: Among the primary health benefi ts associated with community garden ing are improvements in the healthfulness of gardeners' diets and the amount of physical activity . Community garden s can make it easier for participants to adopt healthier behaviors because they can provide greater access to fruits and vegetables, increase preferences for fruits and vegetables, and serve as safe places for physical activity, social support , emotional attachment , and connection with nature and community (Alaimo et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Further, Mell (2010) observed that the definitions of green infrastructure adopted by authors reflect their area of interest in green infrastructure research. For instance, recreational and landscape specialists usually focus on the benefits derived from contact with nature (Dipeolu et al, 2021;Frumkin et al, 2017;Jiang et al, 2018), and urban planners and managers are mostly attracted to the policy implementation aspect (Alaimo et al, 2016;Austin, 2014), while conservationists and ecological specialists tend to articulate the ecological and biodiversity components of green infrastructure (Benedict et al, 2012;Naumann et al, 2011). Although the definitions and components of urban green infrastructure may vary, green infrastructure is described as natural or semi-natural urban environments having a reasonable quantity of green spaces (Dipeolu et al, 2021;Wolch et al, 2014;Zhang et al, 2017).…”
Section: Urban Green Infrastructurementioning
confidence: 99%
“…Further, Mell (2010) observed that the definitions of green infrastructure adopted by authors reflect their area of interest in green infrastructure research. For instance, recreational and landscape specialists usually focus on the benefits derived from contact with nature (Dipeolu et al, 2021;Frumkin et al, 2017;Jiang et al, 2018), and urban planners and managers are mostly attracted to the policy implementation aspect (Alaimo et al, 2016;Austin, 2014), while conservationists and ecological specialists tend to articulate the ecological and biodiversity components of green infrastructure (Benedict et al, 2012;Naumann et al, 2011). Although the definitions and components of urban green infrastructure may vary, green infrastructure is described as natural or semi-natural urban environments having a reasonable quantity of green spaces (Dipeolu et al, 2021;Wolch et al, 2014;Zhang et al, 2017).…”
Section: Urban Green Infrastructurementioning
confidence: 99%
“…The increase in urban food production has been associated with a wide range of benefits. From a public health perspective, urban agriculture has been linked to improved nutrition, higher levels of physical activity, benefits associated with exposure to nature, and increased food security (Davis et al, 2011; Park et al, 2011; Carney et al, 2012, Alaimo et al, 2015, Gonzalez et al, 2015; Smith, 2015). Social benefits, including improved understanding of natural processes and increased social capitol, have also been documented (Okvat and Zautra, 2011; Carney et al, 2012; Pencke, 2015).…”
Section: Benefits Associated With Urban Agriculturementioning
confidence: 99%